Geoquímica e Isotópos de Nd de Rochas Metavulcânicas da Antiforme Capané, Complexo Metamórfico Porongos, RS - GOLLMANN, KARINE; MARQUES, JULIANA CHARÃO; FRANTZ, JOSÉ CARLOS; JUNIOR, FARID CHEMALE (Pesquisas em Geociências, 2008)
The Capané Antiform, located in the northern part of the Neoproterozoic Porongos Metamorphic Complex (RS), is composed of a supracrustal sequence metamorphosed under greenschist (eastern flank) to amphibolite (western flank) facies. Four groups of rocks were recognized. Groups 1 and 2 are constituted of felsic and mafic rocks from the central and western part of the antiform, respectively. They show high LREE and LILE and low HREE and HFSE. The εNd (t) varies from strongly negative (-20) in felsic rocks to moderately negative (-6 to -11) in mafic rocks, with Nd TDM ages that varies from Paleoproterozoic to Mesoproterozoic. The Group 3 consists of metarhyolites from the eastern flank and is geochemically similar to former groups, but shows differences in Nd isotope composition. The εNd(t) is slightly negative (-2 to -4) and the model ages are restricted to the Mesoproterozoic. Group 4, constituted of metabasalts, shows chemical similarities with OIB-MORB and has juvenile isotope signature. The first three groups were interpreted as evolved from a magmatic arc, related probably to the collision of the São Gabriel block with the Encantadas microcontinent during the Neoproterozoic. The Nd differences observed were considered as a result of more or less interaction between mantle and crust components and, particularly, the characteristics observed in the Group 3 can point out a correlation with the syn-tangential granitoids from the eastern part of the Dom Feliciano Belt. The metabasalts of the group 4 were correlated to the antiform’s previously described ophiolite remains.